The Cytolethal Distending Toxin Contributes to Microbial Virulence and Disease Pathogenesis by Acting As a Tri-Perditious Toxin - Scuron, Monika D.; Boesze-Battaglia, Kathleen; Dlakić, Mensur; Shenker, Bruce J. (Frontiers in Cellular and Infection Microbiology, 2016)
This review summarizes the current status and recent advances in our understanding of the role that the cytolethal distending toxin (Cdt) plays as a virulence factor in promoting disease by toxin-producing pathogens. A major focus of this review is on the relationship between structure and function of the individual subunits that comprise the AB2 Cdt holotoxin. In particular, we concentrate on the molecular mechanisms that characterize this toxin and which account for the ability of Cdt to intoxicate multiple cell types by utilizing a ubiquitous binding partner on the cell membrane. Furthermore, we propose a paradigm shift for the molecular mode of action by which the active Cdt subunit, CdtB, is able to block a key signaling cascade and thereby lead to outcomes based upon programming and the role of the phosphatidylinositol 3-kinase (PI-3K) in a variety of cells. Based upon the collective Cdt literature, we now propose that Cdt is a unique and potent virulence factor capable of acting as a tri-perditious toxin that impairs host defenses by: 1) disrupting epithelial barriers; 2) suppressing acquired immunity; 3) promoting pro-inflammatory responses. Thus Cdt plays a key role in facilitating the early stages of infection and the later stages of disease progression by contributing to persistence and impairing host elimination.